Some Observations on Avifauna with Respect to Habitat in Udaipur District, Rajasthan - Banerjee, Arijit (Indian Forester, 1996)
The Southern Aravallis in terms of bird habitat have over the years been a ’dynamic habitat’. While today rangeland species dominate in numbers, the ’habitat islands’ of woodlands prove to be a home for a variety of avifauna. Contrary to the common postulation that with the increase in seral stages, the variety of species increases, despite retrogressive evolution, species variety has not been affected except in composition. The new plantations in Udaipur will prove to be new niches for a variety of woodland species.